Palaeoclimatic impact on the flood basin accretion and palaeosol development in northwestern Bangladesh (Journal of Nepal Geological Society, 1998)
During the Quaternary period, a number of climatic fluctuations occurred as evidenced in the deep-sea core samples, palaeolake deposits, continuous loess profiles in China and glacial deposits in various parts of the world. The fluctuations in palaeoclimatic conditions have influenced eustatic sea-level changes as well resulting in the formation of different sediment facies and landscape evolution worldwide. In the northwestern part of Bangladesh, a thick Pleistocene alluvial sequence has left signatures of these climatic changes. Based on different field criteria such as destratification, horizon formation, colour, biogenic pedogenic features (i.e. rootlets or root traces, burrows, CaCO3 nodules, Fe concretions) and soil structures, 10 buried palaeosols have been recognised in the Pleistocene deposits. The odd numbered palaeosols (i.e., GS1 , GS3, GS5, GS6 and GS9) are designated as moderately developed palaeosols as inferred from their relatively finer textures, higher concentration of pedogenic soil carbonate nodules and lower abundance of iron oxides. The even numbered palaeosols (i.e., GS2, GS4, GS6, GS8 and GS 10) are strongly developed palaeosols, containing very few or no pedogenic carbonate. They also contain Fe oxide concretions, burrows and root channels. Both moderately developed and strongly developed palaeosols occur in cyclic succession. Strongly developed palaeosols occur in thick sediment sequences, which indicate that the flood basin accretion rate was quite high as a result of stronger hydrodynamic conditions. They are the direct consequence of bigger flood events. The relatively thinner sediment sequences, in which the palaeosols are moderately developed, are a consequence of consecutive smaller flood events under drier conditions. Hence, 10 buried palaeosols suggest that at least 10 alternating dry and wet climatic phases prevailed during the successive phases of both palaeosol development and sedimentation cycles. These alternating dry and wet climatic cycles most probably influenced the strengthening and/or weakening of the palaeo-summer moonson. Moreover, studies based on isotopic compositions of stable carbon and oxygen as derived from the analysis on pedogenic carbonate nodules, as well as from the measured bulk magnetic susceptibility in the palaeosol sequences, are found to be in good agreement with the above statement on the dry and wet phases.